Modelling national transformations to achieve the SDGs within planetary boundaries in small island developing states - Cameron Allen; Graciela Metternicht; Thomas Wiedmann; Matteo Pedercini (Global Sustainability, 2021)
Non-technical summary The Sustainable Development Goals (SDGs) provide an integrated and ambitious roadmap for sustainable development by 2030. National implementation will be crucial and there is an urgent need to understand the scale and pace of transformations to achieve the goals. There is also concern that achieving socio-economic objectives will undermine longer-term environmental sustainability. This study uses modelling to explore how different policy and investment settings can enable the necessary transformations, adopting Fiji as a use-case. Modest investment over the coming decade can deliver improved performance. However, far more ambitious actions are needed to accelerate progress while managing long-term trade-offs with environmental objectives.